ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA KEUANGAN BERDASARKAN MODEL POLYA SISWA SMK NEGERI 6 JEMBER - Masrurotullaily, M; Hobri, H; Suharto, S (KadikmA, 2013)
Abstract.Polya Model is one of the problem solving model which consisting four phrases:understanding problem, devising plan, carrying out the plan, and looking back. The purpose of this research is to know the percentage of studentsâ problem solving ability on the subject of financial mathematics based on Polya model. The subject of the research is grade XI Accounting 1 and XI Marketing 1 SMKN 6 Jember. The data collection methodsused in this research are test, interview, and documentation.The result of the research showed that the percentages of students ability which is high, medium and low in problem solving on the subject of financial mathematics based on Polya model generally are 52,97%, 15,87% and 30,16%.It can be concluded that the ability of studentsâ problem solving based on Polya model is high enough on the subject of financial mathematics in SMKN 6 Jember. Key Words : Polya Model, studentsâ problem solving ability, financial mathematics